Audit evidence in a tax audit and methods of its collecting (Journal of Economic Research & Business Administration, 2016)
Actual task of the theory and methodology of tax audit at the present stage is development and deployment of the specific receptions of its organization which are sent to satisfaction of inquiries of users of information on various levels of hierarchy. During carrying out tax audit the audit organization has to obtain the sufficient appropriate evidence with the aim of formations of valid conclusions for an objective demostration of the opinion concerning reliability of charge and payment of taxes and other payments in the budget. In article are considered the concept of auditor evidence and its types, procedures of obtaining auditor proofs and methods of obtaining auditor proofs on the basis of existence of parallel systems tax and accounting.
Keywords: Audit; tax audit; international standards on auditing; evidence; procedures; inspection; observation; inquiry; confirmation; analytical procedures.